Application Potential of Plant-Derived Medicines in Prevention and Treatment of Platinum-Induced Peripheral Neurotoxicity - Xu, Xiaowei; Jia, Liqun; Ma, Xiaoran; Li, Huayao; Sun, Changgang (Frontiers in Pharmacology, 2022)
As observed with other chemotherapeutic agents, the clinical application of platinum agents is a double-edged sword. Platinum-induced peripheral neuropathy (PIPN) is a common adverse event that negatively affects clinical outcomes and patients’ quality of life. Considering the unavailability of effective established agents for preventing or treating PIPN and the increasing population of cancer survivors, the identification and development of novel, effective interventions are the need of the hour. Plant-derived medicines, recognized as ideal agents or safe for usage, can not only help improve PIPN without affecting chemotherapy efficacy, but may also produce synergy. In this review, we present a brief summary of the mechanisms of platinum agents and PIPN and then focus on exploring the preventive or curative effects and underlying mechanisms of plant-derived medicines, which have been evaluated under platinum-induced neurotoxicity conditions. We identified 11 plant extracts as well as 17 plant secondary metabolites, and four polyherbal preparations. Their effects against PIPN are focused on oxidative stress and mitochondrial dysfunction, glial activation and inflammation response, and ion channel dysfunction.Also, ten clinical trials have assessed the effect of herbal products in patients with PIPN. The the understanding of the molecular mechanism is still limited, the quality of clinical trials need to be further improved, and in terms of their efficacy, safety, and cost effectiveness studies have not provided sufficient evidence to establish a standard practice. But plant-derived medicines have been found to be invaluable sources for the development of natural agents with beneficial effects in the prevention and treatment of PIPN.